Cancer gene therapy through autonomous parvovirus - mediated gene transfer - Cornelis, Jan; Dinsart, Christiane; Rommelaere, Jean (Current gene therapy, 2004)
Parvoviruses are small nuclear replicating DNA viruses. The rodent parvoviruses are usually weakly pathogenic in adult animals, bind to cell surface receptors which are fairly ubiquitously expressed on cells, and do not appear to integrate into host chromosomes during either lytic or persistent infection. The closely related rodent parvoviruses MVM, H-1 and LuIII efficiently infect human cell lines. Most interesting, malignant transformation of human and rodent cells was often found to correlate with a greater susceptibility to parvovirus-induced killing (oncolysis) and with an increase in the cellular capacity for amplifying and / or expressing the incoming parvoviral DNA. These and other interesting properties make these autonomous rodent parvoviruses and recombinant derivatives promising candidate antitumor vectors. Capsid replacement vectors have been produced from MVM or H-1 virus that carry transgenes encoding either therapeutic products (cytokines / chemokines, Apoptin, herpes simplex virus thymidine kinase) or marker proteins (green fluorescent protein, chloramphenicolacetyl transferase, luciferase). This review describes the current state of the art regarding the potential application of wild-type parvoviruses and derived vectors for the treatment of cancer. In particular, recent successes with the development of replication-competent virusfree vector stocks are discussed and results from pre-clinical studies using recombinant parvoviruses transducing various cytokines / chemokines are presented.